High-performance liquid chromatographic assays for protoporphyrinogen oxidase and ferrochelatase in human leucocytes - Guo, Rong; Lim, C.K.; Peters, T.J. (Journal of chromatography. Biomedical applications, 1991)
Rapid, sensitive and specific high-performance liquid chromatographic assays are described for protoporphyrinogen oxidase and ferrochelatase in human leucocytes. The enzyme reaction products were separated and quantitated by reversed-phase high-performance liquid chromatography with fluorescence detection. The optimal pH for the protoporphyrinogen oxidase assay was 8.6 and the Michaelis constant for protoporphyrinogen IX was 9.78 ± 0.96 μ M (mean ± S.D.). The mean (± S.D.) activity of protoporphyrinogen oxidase in fourteen apparently healthy subjects was 0.146 ± 0.023 nmol protoporphyrin IX per min per mg protein. In one patient with variegate porphyria, the activity was 0.028 nmol protoporphyrin IX per min per mg protein. The optimal pH for ferrochelatase was 7.4 and with protoporphyrin and Zn 2+ as substrates, the Michaelis constants were 1.49 and 8.33 μ M, respectively. The mean activity of ferrochelatase in ten control subjects was 0.24 n M Zn—protoporphyrin or 2.05 n M Zn—mesoporphyrin formed per h per mg protein.